2013
DOI: 10.5194/acp-13-8585-2013
|View full text |Cite
|
Sign up to set email alerts
|

Observations of gas- and aerosol-phase organic nitrates at BEACHON-RoMBAS 2011

Abstract: At the Rocky Mountain Biogenic Aerosol Study (BEACHON-RoMBAS) field campaign in the Colorado front range, July–August 2011, measurements of gas- and aerosol-phase organic nitrates enabled a study of the role of NOx (NOx = NO + NO2) in oxidation of forest-emitted volatile organic compounds (VOCs) and subsequent aerosol formation. Substantial formation of peroxy- and alkyl-nitrates is observed every morning, with an apparent 2.9% yield of alkyl nitrates from daytime RO2 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

16
226
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 193 publications
(246 citation statements)
references
References 84 publications
16
226
4
Order By: Relevance
“…Phys. (Farmer et al, 2010) pRONO 2 (Fry et al, 2013) conservative approach DL=0.1µg m -3 (Bruns et al, 2010) pRONO 2 lower limit pRONO 2 upper limit Figure 9. Vertical profiles of (a) calculated lower and upper limits of organic nitrate mass concentration (approach Sect.…”
Section: Particulate Organic Nitratementioning
confidence: 99%
See 4 more Smart Citations
“…Phys. (Farmer et al, 2010) pRONO 2 (Fry et al, 2013) conservative approach DL=0.1µg m -3 (Bruns et al, 2010) pRONO 2 lower limit pRONO 2 upper limit Figure 9. Vertical profiles of (a) calculated lower and upper limits of organic nitrate mass concentration (approach Sect.…”
Section: Particulate Organic Nitratementioning
confidence: 99%
“…Polluted urban regions are often dominated by inorganic nitrates (Farmer et al, 2010). However, in rural forested areas a dominance of particulate organic nitrates formed from oxidation of monoterpenes was reported (Fry et al, 2013). A recent 25 study from the Amazon showed with measurements at ground level that up to 87 % of the total nitrate can be attributed to organic nitrate .…”
mentioning
confidence: 99%
See 3 more Smart Citations